Fabrication of H2S gas sensors using ZnxCu1-xFe2O4 nanoparticles - Mohammad Abu Haija (14150478) (2020)
Spinel ferrite nanoparticles can be easily retrieved and utilized for multiple cycles due to their magnetic properties. In this work, nanoparticles of a  ZnxCu1-xFe2O4  composition were synthesized by employing a sol–gel auto-combustion technique. The morphology, composition, and crystal structure were examined using scanning electron microscopy, infrared spectroscopy, and X-ray diffraction. The produced nanoparticles are in the range of 30–70 nm and manifest spinel cubic structure. The nanoparticles were tested for their sensitivity to H2 and H2S gases, and the Cu-based spinel ferrite nanoparticles were found the most sensitive and selective to H2S gas. Their enhanced response to H2S gas was attributed to the production of metallic CuFeS2 that manifest higher electrical conductivity as compared with CuFe2O4. The fabricated sensors are functional at low temperatures, and consequently, they need low operational power. They are also simple to fabricate with appropriate cost. Other Information Published in: Applied Physics A License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00339-020-03661-9